Catalyst for selective hydrogenation and method for its preparation and use

CN118002114BActive Publication Date: 2026-10-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211322518.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2026-10-13
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

[0004]虽然这些催化剂在乙烯选择性方面更有优势,但是要想实现乙炔的完全转化仍需要较高的反应温度,无法满足工厂的实际反应条件

Benefits of technology

[0093]本发明的载体A+载体B之间具有协同作用,其制备的复合载体对应的催化剂的效果更好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003911119090000091
    Figure BDA0003911119090000091
  • Figure BDA0003911119090000092
    Figure BDA0003911119090000092
  • Figure BDA0003911119090000101
    Figure BDA0003911119090000101
Patent Text Reader

Abstract

The application discloses a catalyst for selective hydrogenation and a preparation method and application thereof. The catalyst comprises a composite carrier and an active component loaded on the composite carrier; the composite carrier comprises carrier A and carrier B, the carrier A is graphene-coated nanodiamond, the carrier B is at least one of inorganic oxide, diatomite and molecular sieve; the active component comprises a main active component and an auxiliary active component; the main active component comprises a palladium element; and the auxiliary active component comprises at least one of iron, cobalt, nickel, copper and zinc elements. The catalyst can be directly used in a hydrogenation reaction, and the conversion rate and selectivity of acetylene selective hydrogenation to ethylene are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of selective hydrogenation catalyst technology, and more specifically, to catalysts for selective hydrogenation, their preparation methods, and applications. Background Technology

[0002] Ethylene is one of the most important basic raw materials in the petrochemical industry, produced by cracking gaseous or liquid hydrocarbons. Ethylene produced by cracking contains trace amounts of alkynes, which are detrimental to subsequent reactions such as polymerization. For example, in the production of polyethylene, the presence of alkynes not only degrades polymer properties but can also pose an explosion hazard. Therefore, selective catalytic hydrogenation is typically used in ethylene production processes to remove alkyne concentrations to very low levels (mole fraction < 1 × 10⁻⁶). -6 To meet the requirements of polymerization raw materials, the petrochemical industry is placing increasingly higher demands on the performance of acetylene selective hydrogenation catalysts, as production processes advance and subsequent processes demand higher purity of raw materials. While currently used industrial catalysts can meet the conversion requirements of polymerization, their selectivity still needs improvement.

[0003] In recent years, with the development of catalyst preparation technology, many novel catalysts have been prepared to catalyze the selective hydrogenation of acetylene, enabling complete conversion of acetylene while maintaining good reaction selectivity. For example, Yuan et al. prepared a Ni / MgAl2O4 catalyst using hydrotalcite, achieving complete acetylene conversion at 140℃ while maintaining an ethylene selectivity of 80% (doi.org / 10.1016 / j.jcat.2022.09.005). Zhou et al. prepared a single-atom catalyst using nitrogen-doped graphene support, achieving a 99% acetylene conversion at 125℃ with an ethylene selectivity exceeding 90% under photothermal synergistic effects (10.1002 / adma.201900509).

[0004] Although these catalysts are more selective for ethylene, they still require higher reaction temperatures to achieve complete conversion of acetylene, which cannot meet the actual reaction conditions of the plant. Summary of the Invention

[0005] To address the problems in existing technologies, this invention proposes a catalyst for selective hydrogenation, its preparation method, and its application. The catalyst support of this invention is a mixture of graphene-coated nanodiamond support and other components. The main active component is palladium, and the co-active component contains at least one element selected from iron, cobalt, nickel, copper, and zinc. The catalyst of this invention can be directly used in hydrogenation reactions, improving both the conversion rate and selectivity of acetylene selective hydrogenation to ethylene.

[0006] One objective of this invention is to provide a catalyst for selective hydrogenation, the catalyst comprising a composite support and an active component supported on the composite support;

[0007] The composite carrier includes carrier A and carrier B, wherein carrier A is graphene-coated nanodiamond.

[0008] The carrier B is at least one of inorganic oxides, diatomaceous earth, and molecular sieves;

[0009] The active components include a main active ingredient and a co-active ingredient;

[0010] The main active ingredient includes palladium.

[0011] The co-active ingredients include at least one of the elements iron, cobalt, nickel, copper, and zinc.

[0012] In this invention, there are no special requirements for the shape of the carrier B, but it is preferred to use a carrier with irregular strip shapes such as spherical, sheet-like, toothed spherical, strip-like, clover-like, or four-leaf clover-like.

[0013] In the catalyst for selective hydrogenation described in this invention, preferably,

[0014] Based on the total weight of the catalyst, the content of the active component is 0.001-10 wt%.

[0015] The content of the composite carrier is 90-99.999 wt%;

[0016] Preferably, based on 100% of the total weight of the catalyst,

[0017] The content of the active ingredient is 0.01-2 wt%;

[0018] The content of the composite carrier is 98-99.99 wt%.

[0019] In the catalyst for selective hydrogenation described in this invention, preferably,

[0020] Based on the weight of carrier A and carrier B as 100%, the proportion of carrier A is 5-40 wt%.

[0021] Preferably, the specific surface area of ​​the composite carrier is 1-400 m². 2 / g.

[0022] In the catalyst for selective hydrogenation described in this invention, preferably,

[0023] The inorganic oxide is selected from at least one of Al2O3, SiO2, TiO2, and MgO.

[0024] In the catalyst for selective hydrogenation described in this invention, preferably,

[0025] In the catalyst, the molar ratio of the metal element in the co-active component to the metal element in the main active component is (0.01-50):1; preferably (0.1-10):1.

[0026] In the catalyst for selective hydrogenation described in this invention, preferably,

[0027] The preparation method of the graphene-coated nanodiamond includes the following steps:

[0028] The nanodiamonds prepared by detonation were calcined under a protective atmosphere to obtain the graphene-coated nanodiamonds.

[0029] In the catalyst for selective hydrogenation described in this invention, preferably,

[0030] The graphene-coated nanodiamond has a core-shell structure with graphene as the shell and nanodiamond as the core; in the core-shell structure, the number of graphene shell layers is 1-3.

[0031] In the catalyst for selective hydrogenation described in this invention, preferably,

[0032] The nanodiamond has a particle size of 10–200 nm; and / or,

[0033] The calcination temperature is 900–1500 °C; and / or,

[0034] The roasting time is 1 to 8 hours;

[0035] Preferably,

[0036] The calcination temperature is 900–1200°C; and / or,

[0037] The roasting time is 3 to 6 hours.

[0038] The selective hydrogenation catalyst described in this invention can be analyzed using X-ray photoelectron spectroscopy (XPS) to confirm the chemical valence state of the active component of the catalyst; the particle size and particle size distribution of the active component can be observed using transmission electron microscopy (TEM); and the distribution of the active component on the surface and cross-section of the support can be observed using scanning electron microscopy (SEM).

[0039] A second objective of this invention is to provide a method for preparing the catalyst for selective hydrogenation as described in one objective of this invention, comprising the following steps:

[0040] The catalyst is prepared by loading the metal element corresponding to the active component onto the composite support and then performing post-processing.

[0041] Preferably, the precursor compound solution of the active component is loaded onto the composite support by impregnation or deposition precipitation, followed by post-treatment to obtain the catalyst;

[0042] The precursor compound solution of the active component includes a solution of the precursor compound of the main active component and a solution of the precursor compound of the auxiliary active component.

[0043] In the preparation of the catalyst of the present invention, the active component palladium can be loaded onto the support by impregnation or deposition precipitation. In the present invention, the palladium-containing compound is pre-prepared as a solution, and the solvent is selected from one or more of water, hydrochloric acid, nitric acid, acetic acid, and alcohol; more preferably, the solvent is water.

[0044] In this invention, the compound containing the co-active metal M is pre-prepared as a solution, and the solvent is selected from one or more of water, hydrochloric acid, nitric acid, acetic acid, and alcohol. More preferably, the solvent is water.

[0045] In the method for preparing the catalyst for selective hydrogenation described in this invention, preferably,

[0046] The precursor compound of the main active component is selected from palladium salts; preferably, the palladium salt is selected from at least one of inorganic palladium salts and organic palladium salts; and / or,

[0047] The precursor compound of the active component is selected from the soluble metal salt corresponding to the metal element in the active component, preferably at least one of the nitrate, chloride, and sulfate of the metal element in the active component;

[0048] Preferably,

[0049] The inorganic palladium salt is selected from at least one of palladium chloride, palladium nitrate, and palladium sulfate; and / or,

[0050] The organic palladium salt is selected from at least one of palladium acetate and palladium acetylacetonate.

[0051] In the method for preparing the catalyst for selective hydrogenation described in this invention, preferably,

[0052] In the precursor compound solution of the active component

[0053] Assuming the sum of the mass of the metal elements in the precursor compound of the active component and the composite support is 100%,

[0054] The content of metal elements in the precursor compound of the active component is 0.001-10 wt%; preferably 0.01-2 wt%.

[0055] Preferably,

[0056] The molar ratio of the metal element in the precursor compound of the co-active component to the metal element in the precursor compound of the main active component is (0.01-50):1; preferably (0.1-10):1.

[0057] In the method for preparing the catalyst for selective hydrogenation described in this invention, preferably,

[0058] The solvent in the precursor compound solution of the main active component is selected from at least one of inorganic solvents and organic solvents; and / or,

[0059] The post-processing includes washing and drying.

[0060] Preferably,

[0061] The inorganic solvent is selected from at least one of water, hydrochloric acid, and nitric acid; and / or,

[0062] The organic solvent is selected from at least one of acetic acid and ethanol; and / or,

[0063] The drying temperature in the post-treatment is 50–200°C; and / or,

[0064] The drying time in the post-treatment is 5 to 48 hours;

[0065] More preferably,

[0066] When the inorganic solvent is selected from hydrochloric acid aqueous solution, the molar concentration of the hydrochloric acid aqueous solution is 0.001-0.1; and / or,

[0067] When the inorganic solvent is selected from an aqueous solution of nitric acid, the molar concentration of the aqueous nitric acid solution is 0.001-0.1; and / or,

[0068] The drying temperature in the post-treatment is 80–120°C; and / or,

[0069] The drying time in the post-treatment is 5 to 24 hours.

[0070] In the method for preparing the catalyst for selective hydrogenation described in this invention, preferably,

[0071] The impregnation method includes the following steps: mixing the vacuum-treated composite support with a palladium-containing precursor compound solution, impregnating and stirring, and drying to obtain the catalyst.

[0072] In this invention, the impregnation method can be either a one-step impregnation method or a stepwise impregnation method. When using a one-step impregnation method, the palladium-containing compound and the compound containing the auxiliary metal active component M are dissolved in the same solution to impregnate the support. For precursors where the palladium-containing compound and the compound containing the auxiliary metal active component M cannot be formulated into the same solution, a stepwise impregnation method is preferred. When using a stepwise impregnation method, the palladium-containing compound and the compound containing the auxiliary metal active component M are separately formulated into solutions to impregnate the support.

[0073] In this invention, the impregnation can be a conventional method in the art, such as equal-volume impregnation or supersaturated impregnation. When using supersaturated impregnation, if the active component precursor in the impregnation solution cannot be completely adsorbed by the carrier, the volume of the impregnation solution and the concentration of the active component should be determined according to the adsorption ratio to ensure that the content of the active component loaded on the carrier meets the predetermined requirements. The active component precursor in this invention is a metal compound corresponding to the active component, preferably selected from chlorides, nitrates, acetates, sulfates, and organometallic compounds.

[0074] In the method for preparing the catalyst for selective hydrogenation described in this invention, preferably,

[0075] The composite carrier is prepared by mixing carrier A, carrier B and adhesive, and then molding to obtain the composite carrier.

[0076] Preferably, the adhesive is selected from at least one of carboxymethyl cellulose, polyvinyl alcohol, and starch; and / or,

[0077] The content of the adhesive is 1 to 30 wt%, with the sum of the weights of carrier A and carrier B being 100%.

[0078] The molding process conditions of this invention are common molding methods, preferably compression molding, extrusion molding, spray drying molding, oil molding, spray granulation molding, cooling granulation molding, and fibrous carrier molding, etc. The molding conditions can be selected from commonly used molding parameters.

[0079] A third objective of this invention is to provide the application of the catalyst described in one objective of this invention or the catalyst prepared by the preparation method described in another objective of this invention in the selective hydrogenation of C2 fraction to ethylene.

[0080] In the application described in this invention, the reactor is a conventional hydrogenation reactor in the art. In this invention, the reaction conditions can be conventional temperature, pressure, and space velocity, etc., preferably...

[0081] The molar fraction of acetylene in the C2 fraction is 1.0–5.0%;

[0082] The temperature for selective hydrogenation reactions is 20–120 °C;

[0083] The space velocity for selective hydrogenation reactions is 2000–18000 h⁻¹. -1 ;

[0084] Preferably,

[0085] The molar fraction of acetylene in the C2 fraction is 1–5%;

[0086] The temperature for selective hydrogenation reactions is 40–100 °C;

[0087] The space velocity for selective hydrogenation reactions is 4000–12000 h⁻¹. -1 .

[0088] In the application described in this invention, preferably:

[0089] (A) The above-mentioned catalyst for the selective hydrogenation of acetylene to ethylene is loaded into the reactor;

[0090] (B) The feed gas containing acetylene is introduced into the reactor to carry out the selective hydrogenation reaction of acetylene.

[0091] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values; these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In the following, various technical solutions can, in principle, be combined with each other to obtain new technical solutions, which should also be considered as specifically disclosed herein.

[0092] Compared with the prior art, the present invention has at least the following advantages:

[0093] The carriers A and B of this invention have a synergistic effect, and the catalysts corresponding to the composite carriers prepared by them have better performance.

[0094] The catalyst of this invention still exhibits good catalytic performance at low temperatures, making it suitable for industrial production. Detailed Implementation

[0095] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0096] It should also be noted that the various specific technical features described in the following embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the various possible combinations will not be described separately in this invention.

[0097] Furthermore, various embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention. The resulting technical solutions are part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0098] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0099] The nanodiamonds prepared by the detonation method used in this embodiment of the invention were purchased from Beijing Guoruisheng Technology Co., Ltd.

[0100] Preparation Example 1

[0101] Preparation method of graphene-coated nanodiamonds:

[0102] Nanodiamonds prepared by detonation were calcined under nitrogen at a temperature of 1400℃ for 6 hours to obtain graphene-coated nanodiamonds. The graphene-coated nanodiamonds prepared by the above method have a core-shell structure with graphene as the shell and nanodiamond as the core; in the core-shell structure, the number of graphene shell layers is 1-3.

[0103] Preparation Example 2

[0104] Preparation method of composite carrier:

[0105] The composite carrier A (graphene-coated nanodiamond prepared in Preparation Example 1), carrier B, and binder carboxymethyl cellulose were mixed, cooled, granulated, and shaped to obtain the composite carrier; the specific composition of the composite carrier is shown in Tables 1 and 3.

[0106] Example 1

[0107] Weigh 5.7 g of the composite carrier and vacuum for 10 min. Measure Pd. 2+ A 0.4 mg / mL Pd(NO3)2 solution and a certain amount of Cu 2+A 1 mg / mL Cu(NO3)2 solution was mixed and diluted with deionized water to 50 mL. This solution was added dropwise to the support, and the mixture was impregnated and stirred at 40 °C for 5 h. After cooling to room temperature, 40 mL of C2H5OH was added to the solution, and the solvent was removed using a rotary evaporator. The resulting catalyst was then dried in a 60 °C oven for 12 h. The final catalyst, labeled Catalyst A, was prepared, and its specific composition is shown in Table 2.

[0108] Examples 2-4

[0109] The method of Example 1 was followed, except that the carrier mixed with the graphene-coated nanodiamond carrier was different, and the proportions of added Pd metal and auxiliary metal M were different. The prepared catalysts were labeled as catalyst B, catalyst C and catalyst D, respectively, and their specific compositions are shown in Table 2.

[0110] Table 1

[0111]

[0112] Table 2

[0113]

[0114]

[0115] Example 5

[0116] Weigh 7g of the composite carrier and vacuum for 10 minutes. Measure a certain amount of Co. 2+ A 1 mg / mL CoCl2 solution was diluted with deionized water to 20 mL and then added dropwise to the carrier. The mixture was then incubated and stirred at 40 °C for 5 h. After cooling to room temperature, the solution was removed using a rotary evaporator, and then dried in an oven at 60 °C for 12 h. Pd was measured... 2+ A 0.4 mg / mL Pd(NO3)2 solution was diluted to 20 mL and added dropwise to the dried sample. The sample was then impregnated and stirred at 40 °C for 5 h. After removing the solvent, the sample was dried to obtain catalyst E.

[0117] Examples 6-8

[0118] The method of Example 5 was followed, except that the carrier mixed with the graphene-coated nanodiamond carrier was different, and the proportions of added Pd metal and auxiliary metal M were different. The prepared catalysts were labeled as catalyst E, catalyst F, catalyst G and catalyst H, respectively, and their specific compositions are shown in Table 4.

[0119] Table 3

[0120]

[0121]

[0122] Table 4

[0123]

[0124] In the preparation of the catalyst of the present invention, the content of the active component is calculated according to the fact that the active component is completely adsorbed on the support, and the corresponding amount of palladium nitrate solution (precursor compound solution of the main active component, the concentration of which is 0.4 mg / mL) and precursor compound solution of the auxiliary active component, the concentration of which is 1 mg / mL, are added.

[0125] Comparative Example 1

[0126] A Pd-Ag / Al2O3 catalyst was prepared as a comparative example using the traditional impregnation method. 5 mL of a 10 mg Pd / mL palladium nitrate solution was diluted with water to 70 mL and then impregnated with 100 g of a catalyst with a specific area of ​​30 m² / mL. 2 The catalyst was prepared by placing a spherical Al2O3 support at 120°C and drying it for 8 hours. Then, it was immersed in an aqueous silver nitrate solution (0.047 g of silver nitrate was prepared into 60 mL of silver nitrate solution), dried at 120°C for 8 hours, and calcined at 600°C with air for 4 hours to obtain the Pd-Ag catalyst.

[0127] Comparative Example 2

[0128] The preparation method is basically the same as that of Example 1, except that in Comparative Example 2, the Al2O3 support in Example 1 is replaced with an equal mass of graphene-coated nanodiamond support, denoted as Catalyst I.

[0129] Comparative Example 3

[0130] The preparation method is basically the same as that of Example 1, except that in Comparative Example 2, the graphene-coated nanodiamond support in Example 1 is replaced with an equal mass of Al2O3 support, which is referred to as catalyst II.

[0131] Example 9

[0132] The prepared catalyst was subjected to a simulated microreactor experiment for the post-hydrogenation reaction of acetylene under the following reaction conditions:

[0133] 2g of catalyst was packed into a stainless steel tube reactor with an inner diameter of 2mm. After purging with nitrogen, simulated feed gas from the top of the deethaner was mixed with hydrogen and introduced into the reactor. The composition (mole fraction) of the feed gas was: C2H2: 0.399%, C2H6: 6.04%, C2H4: 43.98%, H2: 0.597%, N2 equilibrium, and the experimental space velocity was 7500 h⁻¹. -1 .

[0134] The selective hydrogenation catalytic performance of the above catalysts for acetylene was evaluated. Catalyst AH in the examples was evaluated directly, catalysts in Comparative Examples 2-3 were evaluated directly, and catalyst in Comparative Example 1 was evaluated after hydrogen reduction. The conversion rates and selectivity of acetylene hydrogenation to ethylene for each catalytic reaction at 80°C are listed in Table 5.

[0135] The conversion and selectivity of ethylene are calculated as follows:

[0136]

[0137]

[0138] Table 5 shows the simulation results of the post-hydrogenation process (average value at 80℃).

[0139]

[0140]

[0141] By comparing Comparative Example 1 with Examples 1-4, it can be seen that the catalyst prepared by the composite support of the present invention has higher selectivity and conversion rate in hydrogenation reaction compared with the commonly used Pd-Ag catalyst. This result fully demonstrates that the catalyst prepared by the composite support of the present invention has better performance.

[0142] Comparing Comparative Example 2 with Example 1, it can be seen that the catalyst prepared by the composite support of the present invention exhibits higher selectivity and conversion rate in the hydrogenation reaction. Comparing Comparative Example 3 with Example 1, it can be seen that the catalyst prepared by the composite support of the present invention exhibits higher selectivity and conversion rate in the hydrogenation reaction. In summary, the above results fully demonstrate that there is a synergistic effect between support A and support B of the present invention, and the catalyst corresponding to the composite support prepared by it has better performance.

[0143] Examples 10-13

[0144] The reaction conditions are basically the same as those in Example 9, except that the reaction temperatures in Examples 10-13 are replaced with 40°C, 70°C, 100°C and 120°C respectively. The specific results are shown in Table 6.

[0145] Table 6. Simulation results of the post-hydrogenation process.

[0146]

[0147] Based on the above data, it can be seen that the catalyst of the present invention does not require a high reaction temperature, and has excellent conversion rate and selectivity even at reaction temperatures below 100°C, meeting the actual reaction conditions of the plant.

[0148] The present invention has been described in detail above with reference to specific embodiments and exemplary examples; however, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A catalyst for selective hydrogenation, characterized in that: The catalyst comprises a composite support and an active component supported on the composite support; The composite carrier includes carrier A and carrier B, wherein carrier A is graphene-coated nanodiamond; the composite carrier is prepared by mixing carrier A, carrier B and adhesive, and then molding to obtain the composite carrier. The carrier B is at least one of inorganic oxides, diatomaceous earth, and molecular sieves; the inorganic oxide is selected from at least one of Al2O3, SiO2, TiO2, and MgO. The active components include a main active ingredient and a co-active ingredient; The main active ingredient includes palladium. The co-active ingredients include at least one of the elements iron, cobalt, nickel, copper, and zinc. Based on the total weight of the catalyst (100%), the content of the active component is 0.01-2 wt%; the content of the composite support is 98-99.99 wt%; based on the weight of support A and support B (100%), the proportion of support A is 5-40 wt%; in the catalyst, the molar ratio of the metal element in the co-active component to the metal element in the main active component is (0.01-50):

1.

2. The catalyst for selective hydrogenation according to claim 1, characterized in that: The specific surface area of ​​the composite carrier is 1-400 m². 2 / g.

3. The catalyst for selective hydrogenation according to claim 1, characterized in that: In the catalyst, the molar ratio of the metal element in the co-active component to the metal element in the main active component is (0.1-10):

1.

4. The catalyst for selective hydrogenation according to claim 1, characterized in that: The preparation method of the graphene-coated nanodiamond includes the following steps: The nanodiamonds prepared by detonation were calcined under a protective atmosphere to obtain the graphene-coated nanodiamonds.

5. The catalyst for selective hydrogenation according to claim 4, characterized in that, The graphene-coated nanodiamond has a core-shell structure with graphene as the shell and nanodiamond as the core; in the core-shell structure, the number of graphene shell layers is 1-3.

6. The catalyst for selective hydrogenation according to claim 4, characterized in that: The nanodiamond has a particle size of 10~200 nm; and / or, The calcination temperature is 900~1500℃; and / or, The roasting time is 1 to 8 hours.

7. The catalyst for selective hydrogenation according to claim 6, characterized in that: The calcination temperature is 900~1200℃; and / or, The roasting time is 3 to 6 hours.

8. The method for preparing a catalyst for selective hydrogenation according to any one of claims 1-7, characterized in that, Includes the following steps: The catalyst is prepared by loading the metal element corresponding to the active component onto the composite support and then performing post-processing.

9. The method for preparing a catalyst for selective hydrogenation according to claim 8, characterized in that... The catalyst was prepared by loading a precursor compound solution of the active component onto the composite support via impregnation and then performing post-treatment. The precursor compound solution of the active component includes a solution of the precursor compound of the main active component and a solution of the precursor compound of the auxiliary active component.

10. The method for preparing a catalyst for selective hydrogenation according to claim 9, characterized in that: The precursor compound of the main active component is selected from palladium salts; and / or, The precursor compound for the active component is selected as a soluble metal salt corresponding to the metal element in the active component.

11. The method for preparing a catalyst for selective hydrogenation according to claim 10, characterized in that: The palladium salt is selected from at least one of inorganic palladium salts and organic palladium salts; and / or, At least one of the metal elements in the active component, namely nitrate, chloride, or sulfate.

12. The method for preparing a catalyst for selective hydrogenation according to claim 11, characterized in that: The inorganic palladium salt is selected from at least one of palladium chloride, palladium nitrate, and palladium sulfate; and / or, The organic palladium salt is selected from at least one of palladium acetate and palladium acetylacetonate.

13. The method for preparing a catalyst for selective hydrogenation according to claim 9, characterized in that: In the precursor compound solution of the active component Assuming the sum of the mass of the metal elements in the precursor compound of the active component and the composite support is 100%, The content of metal elements in the precursor compound of the active component is 0.01-2 wt%.

14. The method for preparing a catalyst for selective hydrogenation according to claim 13, characterized in that: The molar ratio of the metal element in the precursor compound of the auxiliary active component to the metal element in the precursor compound of the main active component is (0.01-50):

1.

15. The method for preparing a catalyst for selective hydrogenation according to claim 14, characterized in that: The molar ratio of the metal element in the precursor compound of the auxiliary active component to the metal element in the precursor compound of the main active component is (0.1-10):

1.

16. The method for preparing a catalyst for selective hydrogenation according to claim 9, characterized in that: The solvent in the precursor compound solution of the main active component is selected from at least one of inorganic solvents and organic solvents; and / or, The post-processing includes washing and drying.

17. The method for preparing a catalyst for selective hydrogenation according to claim 16, characterized in that: The inorganic solvent is selected from at least one of water, hydrochloric acid, and nitric acid; and / or, The organic solvent is selected from at least one of acetic acid and ethanol; and / or, The drying temperature in the post-treatment is 50~200℃; and / or, The drying time in the post-treatment is 5 to 48 hours.

18. The method for preparing a catalyst for selective hydrogenation according to claim 17, characterized in that: The drying temperature in the post-treatment is 80~120℃; and / or, The drying time in the post-treatment is 5 to 24 hours.

19. The method for preparing a catalyst for selective hydrogenation according to claim 9, characterized in that: The composite carrier is prepared by mixing carrier A, carrier B and adhesive, and then molding to obtain the composite carrier. The adhesive is selected from at least one of carboxymethyl cellulose, polyvinyl alcohol, and starch; and / or, The content of the adhesive is 1~30wt%, with the sum of the weights of carrier A and carrier B being 100%.

20. The method for preparing a catalyst for selective hydrogenation according to claim 9, characterized in that: The impregnation method includes the following steps: mixing the vacuum-treated composite support with a palladium-containing precursor compound solution, impregnating and stirring, and drying to obtain the catalyst.

Citation Information

Patent Citations

  • Atomic-scale dispersed palladium-based nanometer diamond / graphene composite material catalyst, preparation method and applications thereof

    CN109174085A

  • Heterogeneous catalyst for selective hydrogenation reaction of alkyne compound and application thereof

    CN109174088A